Shadowing effects on beach morphodynamics during storm events on Tróia-Sines embayed coast, southwest Portugal. - Jacob, José (2009)
The prediction of storm effects on coastline is essential to coastal management and represents a critical issue for the scientific community discussion. In this paper we used SWAN and Méso-NH models to simulate the wave pattern along a ten’s kilometre-scale sandy coastline (TSEC, Tróia-Sines Embayed Coast). The obtained results indicate a shelter effect of the Espichel Cape in the northern half of the TSEC for wave climate from the NWWNW. Under these conditions, the wave height increases in the southward direction and the Setúbal submarine canyon locally influences entire TSEC. The influence of the Espichel Cape and the Setúbal Canyon decreases with the rotation of the wave direction from the NW to W direction. The alongshore wave energy gradient disappears with wave climate from SW and the TSEC is directly exposed to incident waves during storms. The results of modelling seem to explain volumetric changes observed in the TSEC (Tróia, Comporta, Aberta Nova, Santo André and Ribeira de Moinhos), under the effect of seven surveyed storms. Outras publicações